Pita Cukai Digital: Systematic Literature Review, Potensi Dan Tantangan Dalam Pemberantasan Rokok Ilegal Di Indonesia - Yasmina Aziza Astri; Muhammad Yopan (Owner : Riset dan Jurnal Akuntansi, 2025)
Excise duty plays a dual role as a source of state revenue and a regulatory instrument to control the consumption of goods with negative externalities. Unlike other taxes, excise collection requires a physical marker, typically an excise stamp, which also functions as a monitoring tool. With technological advancements, conventional excise stamps have evolved into digital forms incorporating features such as track-and-trace systems, direct marking, or QR codes, which enhance transparency and enforcement by allowing both authorities and the public to verify product authenticity. This study employs a systematic literature review (SLR) to examine the implementation of digital excise stamps in various countries and assess their relevance to the Indonesian context. The findings indicate that digital excise stamps offer significant opportunities for improving excise administration and increasing state revenue. However, challenges remain, including differences in the structure and scale of Indonesia’s tobacco industry, the nature of excise violations, and the high initial investment costs required for implementation. The study provides valuable insights for policymakers considering the adoption of digital excise stamp in Indonesia.